SIRT2 mediated downregulation of FOXM1 in response to TGFβ through the RAF-MEK-ERK signaling pathway in colon cancer - Ozden, Ozkan; Park, Seong-Hoon (Archives of Biological Sciences, 2021)
Paper description: The Forkhead Box M1 (FOXM1) oncogenic transcription factor is upregulated in many malignancies, including colorectal cancer. Removal or silencing of Sirtuin 2 (SIRT2) upregulates FOXM1 through the transforming growth factor-beta (TGFβ mitogen-activated protein kinase (RAF-MEK-ERK) signaling pathway in both SIRT2 knockout mouse embryonic fibroblasts and SIRT2 knocked-down HCT116 colon cancer cells. SIRT2 overexpression in HCT116 cells decreased the number of colony formations and lengthened the doubling time. The intracellular distribution of FOXM1 was independent of SIRT2 overexpression in HCT116 cells. Abstract: The transcription factor forkhead box M1 (FOXM1) is frequently upregulated in many solid tumors, including those in the colon. As a master regulator, the sirtuin (SIRT) protein family is comprised of seven nicotinamide adenine dinucleotide (NAD+)-dependent deacetylases/adenosine diphosphate (ADP) ribosyl transferases whose activities are associated with aging and cancer. In this study, we determined whether a cytoplasmic member of SIRTs, SIRT2, influences the expression of oncogenic FOXM1 in colon cancer in vitro. The association of SIRT2 and FOXM1 were analyzed using SIRT2 knockout mouse embryonic fibroblasts and SIRT2 knocked-down and overexpressing HCT116 colon cancer cell lines. Cell lines were treated with 10 ng/mL transforming growth factor-beta (TGFb) for 24 h. SIRT2 could downregulate FOXM1 through the TGFb mitogen-activated protein kinase (RAF-MEK-ERK) signaling pathway in genetically altered mouse embryonic fibroblasts and colon cancer cell lines. The indirect association between SIRT2 and FOXM1 through TGFb may be important because activators or inhibitors of SIRT2 could provide a potential approach to downregulate FOXM1 in gastrointestinal cancers.